Impact of pediatric COVID-19 isolation on children’s well-being and caregiver mental health - Song I. Yang; Chi-Hyun Choi; Eun Joo Lee; Sun Hee Jee; Mi Seon Han (BMC Pediatrics)
Abstract Background The Korean government implemented mandatory hospital isolation in the early phase of the COVID-19 pandemic. This study investigated the mental health of children and caregivers who underwent mandatory hospital isolation due to COVID-19. Methods This prospective study examined the physical condition and mental health of children under 7 years of age with COVID-19 and the mental health of their caregivers who underwent isolation in negative pressure rooms at two hospitals in Korea from April to September 2021. Caregivers received a self-report questionnaire via text message. Their responses were analyzed to compare the physical condition and mental health of children with COVID-19 and the mental health of their caregivers during and after isolation and identify factors influencing caregivers’ mental health. Results Sixty caregivers participated in the study. More than half of the caregivers perceived their children’s disease severity as mild. During hospital isolation, 36.4% of the children experienced decreased oral intake, which improved significantly post-isolation (8.7%, P = 0.014). During isolation, approximately 22.2% of the children frequently awoke from sleep, 20.0% displayed irritability, and 70.8% had symptoms of depression. Approximately 36.7% of caregivers showed at least moderate levels of depression during isolation, which significantly decreased to 14.3% three months after discharge (P = 0.032). Factors associated with caregivers’ mental health included child-related issues, such as difficulty concentrating, frequent awakenings, and irritability. Conclusion Mandatory hospital isolation has a significantly negative psychological impact on children and caregivers during pandemics. Isolation decisions must be carefully considered during pandemics, especially those concerning young children. Heightened vigilance is warranted for the early detection and intervention of mental health issues in children and their caregivers.